2019
DOI: 10.1038/s41467-019-09344-1
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of functional lateralisation and its relationship to callosal connectivity in the human brain

Abstract: Functional lateralisation is a fundamental principle of the human brain. However, a comprehensive taxonomy of functional lateralisation and its organisation in the brain is missing. Here, we report the first complete map of functional hemispheric asymmetries in the human brain, reveal its low dimensional structure, and its relationship with structural inter-hemispheric connectivity. Our results suggest that the lateralisation of brain functions is distributed along four functional axes: symbolic communication,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
165
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 73 publications
(75 reference statements)
23
165
0
Order By: Relevance
“…In addition, more symmetrical functional organization is found for higher probability in callosal connectivity (Karolis et al 2019) and corresponds to the apexes of the gradient in the present study. This is in line with studies showing that stronger callosal connections are associated with a decrease in perceptual processing asymmetries.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, more symmetrical functional organization is found for higher probability in callosal connectivity (Karolis et al 2019) and corresponds to the apexes of the gradient in the present study. This is in line with studies showing that stronger callosal connections are associated with a decrease in perceptual processing asymmetries.…”
Section: Discussionsupporting
confidence: 81%
“…In order to map the gradient along the white mater connections, we employed the Disconnectome within the BCBtoolkit (Foulon et al 2018) using a study-specific HCP dataset of 163 participants to generate the underlying white matter tractograms (Karolis et al 2019). The scanning parameters have been described previously (Vu et al 2015).…”
Section: Gradient Percentage Mapsmentioning
confidence: 99%
“…In our study, reward responsivity was investigated in the context of decision making. Interestingly, a recent metaanalysis of lateralization of function suggested that decision making rather than emotion, communication, or perception/action is associated with OFC lateralization (16). Although the adaptive consequences of lateralized functions are not well understood, it is thought that hemispheric specialization could increase processing abilities by reducing bilateral redundancy (20).…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetrical OFC responses in healthy subjects have also been reported in functional magnetic resonance imaging (fMRI) studies (for metaanalyses, see refs. 15,16). However, this result has rarely been discussed.…”
mentioning
confidence: 99%
“…On the functional level, neuroimaging studies have indicated major differences in movement-associated activation patterns between the motor-dominant and motor-non-dominant hemispheres 13 , while TMS studies have shown significant interhemispheric differences between the cortical motor representation areas 14 and the stimulation intensities required to elicit motor responses from the two M1 (with the motor-dominant hemisphere typically requiring lower stimulation intensities than the motor-non-dominant hemisphere) 15,16 . On the structural level, alongside interhemispheric differences in transcallosal 17 and cortico-cortical M1 connectivity 18 , significant interhemispheric differences in local intracortical M1 circuits are noted 19 . For example, regional asymmetries of cortical thickness and local gyrification between the hand-knob areas of the two M1 have been associated with the degree of handedness, with evidence of robust leftward asymmetries (i.e., greater gyrification and cortical thickness in the motor-dominant M1) in consistent right-handers 20 .…”
mentioning
confidence: 99%